2019
DOI: 10.1891/wfccn-d-19-00010
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Workplace Bullying in Emergency and Critical Care Nurses in Cyprus

Abstract: BackgroundWorkplace bullying is considered as an extreme work-related stressor, associated with mental and physical burden.AimInvestigation of workplace bullying occurrence and related factors in Greek-Cypriot nurses employed in private and public emergency (emergency departments [EDs]) and critical care settings (intensive care units [ICUs], coronary critical care units [CCCUs]).MethodsA descriptive, cross-sectional correlation study was performed. Following informed consent, a convenience sample of 113 nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Yet, it should be stressed that neither STSS-M nor other similar instruments are diagnostic of PTSD; instead, the focus of relevant instruments is on identifying differences of the experienced PTSD symptoms across time or need for advanced assessment and support. Although the present data identified that a significant percentage of nurses experience debilitating psychological traumas after exposure to workplace bullying/mobbing, it is worth noting that the majority of them still show a tendency towards symptom underestimation and non-treatment seeking behaviors ( Aristidou et al, 2019 ). Moreover, in the present study a vast majority of participants (54/77; see Table 3 ) responded that they avoided reporting the bullying/mobbing experience because of thinking it was not important.…”
Section: Discussionmentioning
confidence: 57%
“…Yet, it should be stressed that neither STSS-M nor other similar instruments are diagnostic of PTSD; instead, the focus of relevant instruments is on identifying differences of the experienced PTSD symptoms across time or need for advanced assessment and support. Although the present data identified that a significant percentage of nurses experience debilitating psychological traumas after exposure to workplace bullying/mobbing, it is worth noting that the majority of them still show a tendency towards symptom underestimation and non-treatment seeking behaviors ( Aristidou et al, 2019 ). Moreover, in the present study a vast majority of participants (54/77; see Table 3 ) responded that they avoided reporting the bullying/mobbing experience because of thinking it was not important.…”
Section: Discussionmentioning
confidence: 57%